Monoterpeno 4-terpineol ─ uma molécula com atividade anticonvulsivante: estudos comportamentais e eletrofisiológicos - Nobrega, Franklin Ferreira de Farias (2012)
Terpinen-4-ol (4TRP) is a monoterpe alcohol and component of the essential oils of several aromatic plants. Similarly to 4TRP, other monoterpenoid alcohols have showed anticonvulsant activity in convulsion animal models. The present report aimed to investigate the psychopharmacological effects of terpinen-4-ol, specifically the anticonvulsant activity. Mice (Mus musculus) swiss male and and rats (Rattus norvegicus) wistar male were used. In experiments in vivo, the 4TRP was administered at doses of 25 to 200 mg/kg, ip, and concentrations of 10, 20 and 40 ng/2μL, icv. For in vitro experiments, concentrations were 0.1 mM and 1.0 mM. General tests as pharmacological behavioral screening, spontaneous movement, potentiation of sleeping time induced by pentobarbital and rota rod test were initially performed to investigate the profile of action of this monoterpene in the CNS. In all these methods, the results suggest that this drug has psycholeptics profile and does not cause significant changes in motor coordination of animals. Next, more specific experiments were performed to evaluate the psicodepressor profile: the elevated plus maze (EPM) test and the perforated plate have been selected to investigate possibleanxiolytic effects. In these experiments, and the doses tested, were not observed consistently indicative of anxiolytic activity related to 4TRP. Later, tests were performed to evaluate the possibility of this substance present a profile of anticonvulsant activity. According to the behavioral parameters evaluated, 4TRP (via ip) was able to inhibit seizures induced by both Pentylenetetrazole (PTZ) and Maximal electroshock (MES), presenting a potential anticonvulsant effect. In a subsequent step, following the animals by electroencephalographic recordings, we observed that animals treated with 4TRP (via icv) were protected against PTZ-induced seizures, corroborating the results of the previous step. In the search for a characterization of the possible mechanisms by which this substance exerts this action, we investigate more clearly the involvement of the GABAergic system employing the methodologies convulsions induced by picrotoxin (PIC) and seizures induced by 3-mercapto-propionic acid (3-MP). In accordance with the results, it is possible to infer that the action exerted by monoterpenoid is related to the GABAergic system and that the presence of flumazenil, a selective antagonist of the benzodiazepine site of GABA A receptors, was unable to reverse the anticonvulsant effect of 4TRP, demonstrating that this is not the same binding site of benzodiazepines. In a subsequent step, using the technique of "Whole-Cell Patch Clamp , demonstrated that 4TRP was able to decrease the sodium current in sodium channels of voltage-dependent in isolated cells of neurons in dorsal root ganglia (DRG), and possibly its effect is related to changes in neuronal excitability in consequence of modulation of these channels. It was concluded that 4TRP has psychopharmacological effects, with an anticonvulsant profile. Its mechanism of action appears to be mediated by interference with the GABAergic system and does not involve activation, at least directly, the benzodiazepine site of GABAA receptors and that involves the blockade of sodiumchannels voltage-dependent.